A molecular dynamics study of catestatin docked on nicotinic acetylcholine receptors to identify amino acids potentially involved in the binding of chromogranin A fragments. Issue 26 (14th July 2015) - Kraszewski, Sebastian; Drabik, Dominik; Langner, Marek; Ramseyer, Christophe; Kembubpha, Sineenat; Yasothornsrikul, Sukkid
<x xml:space="preserve">Abstract</x> Human catestatin, representing potential to regulate nicotinic signal transduction, can bind onto nAChR-β subunits indicating a novel mode of action.